Does endometrial compaction before embryo transfer affect pregnancy outcomes? a systematic review and meta-analysis - Chen, Xiao-Tong; Sun, Zhen-Gao; Song, Jing-Yan (Frontiers in Endocrinology, 2023)
Objective: There is no clear evidence of clinical significance of endometrial compaction, which can be measured by a reduction in endometrial thickness (EMT) during the follicular-luteal transition before the day of embryo transfer. In this study, we aim to determine whether endometrial compaction has an effect on in vitro fertilization (IVF) success. Method (s): We searched PubMed, Cochrane, Embase, and Web of Science electronic databases for studies published in English up to March 2023. Heterogeneity between studies was assessed using the I2 statistic. The random effects model and fixed effects model was used to pool the risk ratio (RR) with a corresponding 95% confidence interval (CI). A subgroup analysis was performed based on different methods of ultrasonic measurement and different endometrial compaction rates (ECR). Stata 17.0 software was used for meta-analysis. Pregnancy outcomes, which included clinical pregnancy rate, ongoing pregnancy rate, live birth rate, and spontaneous abortion rate, were evaluated. Result (s): In this study, 18 cohort studies were included, involving 16,164 embryo transfer cycles. Pooled results indicated that there was no significant difference between the endometrial compaction group and the non-compaction group in terms of clinical pregnancy rate (RR [95% CI]=0.98 [0.90,1.08]; I2=69.76%), ongoing pregnancy rate (RR [95% CI]=1.18 [0.95,1.47]; I2 =78.77%), live birth rate (RR [95% CI]= 0.97 [0.92,1.02]; I2=0.00%) or spontaneous abortion rate (RR [95% CI]= 1.07[0.97,1.26]; I2=0.00%). According to the subgroup analysis of ultrasonic measurement methods, in the transvaginal ultrasound (TVUS) combined with abdominal ultrasonography (AUS) cycles of the endometrial compaction group, the rate of ongoing pregnancy (RR [95% CI] = 1.69 [1.26, 2.26]; I2 = 29.27%) and live birth (RR [95% CI] = 1.27 [1.00,1.61]; I2=62.28%) was significantly higher than that of the non-compaction group. Additionally, subgroup analysis based on ECR revealed a significantly higher rate of ongoing pregnancy when ECR ≥ 15% (RR [95% CI] = 1.99 [1.61, 2.47]; I2=0.00%). Conclusion (s): Endometrial compaction has no adverse effect on clinical pregnancy rate, ongoing pregnancy rate, live birth rate, or spontaneous abortion rate. A possible explanation for the contradictory findings of previous studies lies in the method by which the EMT is measured.